2003
DOI: 10.1103/physrevlett.90.075701
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Phase Relaxation along the Critical Isochore of Nitrogen: The Role of Local Density Fluctuations in the Rate Enhancement

Abstract: Vibrational dephasing of the nitrogen molecule is known to show highly interesting anomalies near its gas-liquid critical point. Here we present theoretical and computational studies of the Raman linewidth of nitrogen along the critical isochore. The linewidth is found to have a lambda-shaped temperature dependence near the critical point. As observed in experimental studies, the calculated line shape becomes Gaussian as the critical temperature (T(c)) is approached. Both the present simulation and a mode coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We have computed the instantaneous frequency shift using this formulation. It has already been found that, for two very different systems (weakly interacting neat N 2 [35] and strongly interacting CN À in H 2 O [36]), the first term dominates the total pure dephasing rate. This is of course the first derivative of the solute-solvent coupling, i.e., forces on the bonded atoms.…”
Section: Theoretical Analysismentioning
confidence: 96%
“…We have computed the instantaneous frequency shift using this formulation. It has already been found that, for two very different systems (weakly interacting neat N 2 [35] and strongly interacting CN À in H 2 O [36]), the first term dominates the total pure dephasing rate. This is of course the first derivative of the solute-solvent coupling, i.e., forces on the bonded atoms.…”
Section: Theoretical Analysismentioning
confidence: 96%
“…23,24 Oxtoby derived the following expression for the time correlation function of the frequency modulation ͑due to atom-atom contributions͒ between two quantum levels n and m in terms of the force-force time correlation function on the atom involved in the bond: 1 In binary mixtures composition fluctuations are obviously expected to play an important role in dephasing akin to the density fluctuations in neat liquid.…”
Section: Mode Coupling Theory Analysismentioning
confidence: 99%
“…13,23,24 The density functional theory approach provides the mode coupling theory expression for the force-force time correlation function ͑see Ref. 12͒ of the atom i moving along the direction of vibration.…”
Section: Mode Coupling Theory Analysismentioning
confidence: 99%
“…12b]. Above T c , the fluctuations [16] are small which cause the resonance lines to be homogeneously broadened and the line shape is Lorentzian. On approaching T c , the fluctuations [35,36] become large and their correlation time also increases, as a consequence the line shape becomes Gaussian.…”
Section: Mode Coupling Theory Analysismentioning
confidence: 99%
“…They reproduced the experimental data semiquantitatively (within 40% in most cases). They have also applied the mode coupling theory (MCT) [13,16] to compare with the simulation results. In their calculations they have not include the vibrational coordinate (q) dependence of the interatomic potential and also ignored the cross-terms among the vibration-rotation coupling term, the atom-atom term, and the resonance term.…”
Section: Introductionmentioning
confidence: 99%